Various factors influencing the development of the Vietnamese real estate market: A case study - Le Trung Dao; Quang Minh Nguyen (Contemporary Economics, 2025)
The outbreak of the Covid-19 epidemic has caused some disruption to the real estate market in Vietnam. To survive the Covid-19 pandemic, real estate businesses have rushed to find alternative solutions, proactively approach support packages, and change business strategies. Moreover, the real estate market is critical and linked to many manufacturing industries and the development of the real estate market attracting resources, creating significant fixed assets for the economy, and contributing to the country's industrialization and modernization. Thus, the paper's main objective is to study various factors influencing the real estate market development in Vietnam. This research conducted a survey using data from 700 investors employed in real estate firms. The survey utilized structural equation modeling and SPSS 20.0, Amos software for data analysis. The study identifies five elements that significantly influence the development of the real estate market and five hypotheses accepted with a significance of 1.0 percent. The article's innovation is in identifying the credit policy component that exerts the greatest influence on the development of the real estate market. Ultimately, the research put forward policy suggestions aimed at fostering a secure, thriving, and environmentally responsible real estate market in Vietnam after the Covid-19 pandemic.
Keywords: G00; O23; R10; R30; 330; credit policy; market developing; real estate; COVID-19; Vietnam